Sobre Hipersuperfícies em Espaços de Curvatura Seccional Constante - Muniz Neto, Antonio Caminha (2004)
The present work is organized in the following way: we establish several notations, as well as collect some elementary results on tensors, Lorentz varieties and isometric immersions. The next chapter is devoted to the study of the average r-curvatures Hr of a hypersurface. In particular, we prove the formulas for Lq (Sr) and Lr (Sr). And in the last chapter, such a formula is applied in the deduction of the aforementioned results.